2020
DOI: 10.21203/rs.2.22947/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cancer development in COPD patients: retrospective analysis of the National Health Insurance Service-National Sample Cohort in Korea

Abstract: Background: COPD is a well-known risk factor for lung cancer, independent of smoking behavior. By investigating the retrospective National Health Insurance Service-National Sample Cohort (NHIS-NSC) in Korea, this study attempted to prove the hypothesis that COPD is a risk factor for major cancers developing outside of the lungs. We also aimed to investigate the environmental factors associated with the development of lung cancer in COPD patients.Methods: This study analyzed data from the NHIS-NSC over a 12-yea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Although the crude incidence rate in patients with COPD was high, we did not find a difference in the overall age-adjusted rate of gastric cancer between patients and the Quebec general population. Previous studies had similar findings (Chiang et al , 2016; Ho et al , 2017; Ahn et al , 2020) and only one study reported an increased risk relative to the general population (Kornum et al , 2012). Despite no difference in the overall rate, the annual IRR rose over the years, due to the growing rate of gastric cancer in patients with COPD and the decreasing rate in the Quebec population.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although the crude incidence rate in patients with COPD was high, we did not find a difference in the overall age-adjusted rate of gastric cancer between patients and the Quebec general population. Previous studies had similar findings (Chiang et al , 2016; Ho et al , 2017; Ahn et al , 2020) and only one study reported an increased risk relative to the general population (Kornum et al , 2012). Despite no difference in the overall rate, the annual IRR rose over the years, due to the growing rate of gastric cancer in patients with COPD and the decreasing rate in the Quebec population.…”
Section: Discussionmentioning
confidence: 73%
“…Globally, COPD is a major contributor to morbidity and mortality, affecting about 251 million people in 2016 and accounting for more than 3 million deaths in 2015 (WHO, 2021). Evidence indicates a strong link between COPD and lung cancer (Durham and Adcock, 2015), with some studies finding an association that is independent of smoking (Young et al , 2009; Ahn et al , 2020). However, less is known about the relationship of COPD with other malignancies, particularly gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Các nghiên cứu này cho thấy AUROC của qSOFA trong việc tiên lượng tử vong dao động trong khoảng 0,6 -0,8. [9][10][11][12] Trên bệnh nhân SARI, nghiên cứu của chúng tôi cho kết quả tương đồng với một nghiên cứu trên 159 bệnh nhân tại Thổ Nhĩ Kỳ (AUROC = 0,683). 13 Nghiên cứu này cũng cho thấy giá trị tiên lượng tử vong của thang điểm qSOFA thấp hơn các thang điểm CURB-65, PSI, và APACHE II (AUROC lần lượt là 0,717; 0,712; và 0,748).…”
Section: Bàn Luậnunclassified
“…Về độ nhạy và độ đặc hiệu, đa số các nghiên cứu khác cho thấy thấy trong việc tiên lượng bệnh nhân điểm qSOFA ≥ 2 có độ nhạy thấp và độ đặc hiệu ở mức trung bình đến cao trong việc tiên lượng tử vong ở bệnh nhân nhiễm trùng. 12,14,15 Thêm vào đó, một phân tích gộp 6 nghiên cứu trên 17868 bệnh nhân viêm phổi cho thấy độ nhạy và độ đặc hiệu tương ứng trong tiên lượng tử vong của qSOFA Hình 1 cho thấy so với những bệnh nhân có qSOFA < 2, thời gian sống thêm của bệnh nhân có qSOFA ≥ 2 giảm một cách đáng kể trong vòng 7 ngày (log-rank test, p < 0,05). trùng.…”
Section: Bàn Luậnunclassified
“…COPD is a risk factor for lung cancer and they have many shared driving factor and genetic effect (Durham and Adcock, 2015). Also, COPD is a risk factor for major cancers developing outside of the lung, including bladder cancer and pancreatic cancer (Divo et al, 2012;Ahn et al, 2020). Furthermore, Angiogenesis (vasculature development) is a shared phenomenon for both cancer and COPD (Matarese and Santulli, 2012), which may indicate the molecular connection between COPD and cancers.…”
Section: Real Applicationmentioning
confidence: 99%